Neoseiulus tunus (De Leon, 1967) (Acari: Phytoseiidae): is this a potential natural enemy of Aculops lycopersici (Massee, 1937) (Acari: Eriophyidae)? - Amaral, Felipe S. R.; Ferreira, Mizael M.; Lofego, Antonio C. (Entomological Communications, 2021)
This study aimed to determine the biological parameters of Neoseiulus tunus (De Leon, 1967) feeding on Aculops lycopersici (Massee, 1937). We conducted experiments to assess the predation rate of the former and its biological cycle when consuming A. lycopersici exclusively. Moreover, we assessed the preference of N. tunus for A. lycopersici concerning the pollen of Typha domingensis Pers. (Typhaceae) and Tetranychus urticae Koch, 1835, using free-choice tests. The obtained data indicates A. lycopersici is an appropriate prey to N. tunus, as it allows it to complete its development, reproduce and increase its population. We also noticed that this phytoseiid prefers A. lycopersici to the two other food sources. Though more robust studies will be needed, these preliminary results allow some inferences, such as N. tunus being a potential natural enemy of A. lycopersici.